The substantive law of the EU : the four freedoms (Oxford Univ. Press, 2010)
"The Substantive Law of the EU by Catherine Barnard is the perfect resource for anyone wishing to gain a thorough grasp of the four freedoms in EU law. An introductory chapter outlines the background to EU law in this area: the role of free trade theory, the evolution and expansion of the internal market and the fundamental principles underpinning this process. The following sections then provide a detailed examination of the four freedoms - goods, persons, services, and capital - which make up the core of EU law. The fully revised and updated third edition addresses the significant recent developments in EU legislation including expanded coverage of the free movement of services and more detailed consideration of the derogations and limitations to the four freedoms. Regular case studies help to unlock the subtleties of EU law in operation and frequent diagrams and flow charts clarify the more complex areas of substantive law. The book is accompanied by an Online Resource Centre providing: An additional chapter on Intellectual property and the free movement of goods - useful for anyone needing to study this topic, An interactive map of Europe with hot-spots on all EU Member States providing factual information on each country, A timeline of the EU tracing key dates in EU legal history * Electronic copies of the figures from the book are available to lecturers for re-use in lectures and as handouts * A treaty navigation resource enabling the user to look first hand at the key primary sources of law and trace its development and evolution * Video clips from the EU archive demonstrate the important historical context to EU law helping students to appreciate the wider aspects of the EU's development * Web links to useful sources of information provide the ideal platform to online research"–
Erg. Materialien online: http://www.oxfordtextbooks.co.uk/orc/barnard3e/